American society : - Wright, Erik Olin (W.W. Norton & Co., 2011)
This book evaluate to what degree contemporary American society realizes these values and suggest how Americans might solve some of the social problems that confront America today. It consists of 3 parts: Capitalism; Inequality; Democracy